2005
DOI: 10.4269/ajtmh.2005.72.236
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Placental Malaria and Its Effect on Pregnancy Outcome in Yaounde, Cameroon

Abstract: Between 1996 and 2001, the prevalence of placental malaria in pregnant women living in Yaounde, Cameroon and its effect on pregnancy outcome were evaluated with respect to gravidity and maternal age. Results showed that 19.9% of the women had placental malaria at delivery. After adjusting for relevant covariates, the major risk factor for placental malaria was an age < 25 years old. Placental malaria significantly increased the prevalence of anemia in women regardless of gravidity or age. In addition, the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
100
5
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 31 publications
17
100
5
4
Order By: Relevance
“…The malaria parasites either directly cause mechanical compromise of placental circulation via widespread trophoblast membrane thickening, increased fibrinoid necrosis and cytotrophoblast prominence or indirectly interfere with placental function and induce pathological lesions. 31 The finding in this study agrees with those of Bako et al, 6 Okoko et al, 24 and Tako et al 18 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The malaria parasites either directly cause mechanical compromise of placental circulation via widespread trophoblast membrane thickening, increased fibrinoid necrosis and cytotrophoblast prominence or indirectly interfere with placental function and induce pathological lesions. 31 The finding in this study agrees with those of Bako et al, 6 Okoko et al, 24 and Tako et al 18 .…”
Section: Discussionsupporting
confidence: 83%
“…18 Higher rates of 33.2% and 53.6% were previously reported by Adebami et al 19 and BouyouAkotet et al 20 in Ile -Ife, Nigeria and Gabon respectively. The lower prevalence reported in this study may be due to the effective malaria control measures employed in the population, which include sulphadoxine -pyrimethamine 20 Several studies have shown that parity influences susceptibility to placental malaria with primigravidae being more susceptible compared to multigravidae.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Factors that influence the prevalence of malaria in pregnant women were identified and include maternal age, parity, use of prophylaxis, nutrition, genetics of the host, level of anti-parasitic immunity and genetics of the parasite 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Malaria contributes significantly to perinatal disease burden in terms of pregnancy loss, prematurity and intra-uterine growth retardation (IUGR) [1][2][3]. Despite these well-documented indirect effects of malaria to the fetus and newborn, the direct burden of neonatal malaria infection in terms of prevalence and outcome is not well described in malaria endemic areas.…”
Section: Introductionmentioning
confidence: 99%